Ответы и объяснения

2012-04-05T05:48:29+00:00

1) 4x + 3y = 5               

    x - y  = 7

   

    4x + 3y = 5               

    x  = 7  + y    /подставляем выражение для х в первое уравнение, получаем:

 

    4(7  + y) + 3y = 5

    28 + 4y + 3y = 5

    28 + 7y = 5 

    7y = 5 - 28

    7y = - 23

     у =  - 23/7

     у =  - 3  2/7    тогда х = 7  + y = 7  - 3  2/7  = 3  5/7

 

Ответ: (3  5/7;  - 3  2/7)

 

2)  6x+5y=6

     x-y=3

 

     6x+5y=6

     x = 3 + у

 

     6(3 + у)+5y=6

     18 + 6у+5y=6

     18 + 11у = 6

     11у = 6 - 18

     11у = - 12

     у = - 12/11

     у = - 1 1/11         тогда   x = 3 + у = 3 - 1 1/11 = 1 10/11

Ответ: ( 1 10/11;  - 1 1/11)

 

3) 5x-3y=1

    2x+y=-2

 

    5x-3y=1    

    y= -2 - 2х

 

    5x-3(-2 - 2х)=1

    5x + 6 + 6х=1

    11x + 6 =1

    11x =1- 6

    11x =-5

    x =- 5/11  , тогда  y= -2 - 2х = -2 - 2(- 5/11 ) = -2 +10/11  =  - 1 1/11

Ответ: ( - 5/11;  - 1 1/11)